Overexpression of Evi‐1 oncoprotein represses TGF‐β signaling in colorectal cancer12. Issue 4 (7th December 2011) - Deng, Xiyun; Cao, Yanna; Liu, Yan; Li, Fazhi; Sambandam, Kamalanathan; Rajaraman, Srinivasan; Perkins, Archibald S.; Fields, Alan P.; Hellmich, Mark R.; Townsend, Courtney M.; Thompson, E. Aubrey; Ko, Tien C.
Abstract Human colorectal cancer (CRC) cells are resistant to the anti‐proliferative effect of transforming growth factor‐β (TGF‐β), suggesting that disruption of TGF‐β signaling plays an important role in colorectal carcinogenesis. Ecotropic virus integration site‐1 (Evi‐1) oncoprotein represses TGF‐β signaling by interacting with Smads, but its role in CRC has not been established. The purpose of this study is to determine whether Evi‐1 plays role(s) in CRCs and to characterize Evi‐1 transcript(s) in CRCs. Evi‐1 was overexpressed in 53% of human CRC samples, 100% of colon adenoma samples, and 100% of human colon cancer cell lines tested. Using 5′ RACE, we cloned a novel Evi‐1 transcript (Evi‐1e) from a human CRC tissue and found that this novel transcript was expressed at a higher level in CRC tissues than in normal tissues and was the major Evi‐1 transcript in CRCs. Transient Evi‐1 transfection inhibited TGF‐β‐induced transcriptional activity and reversed the growth inhibitory effect of TGF‐β in MC‐26 mouse colon cancer cells. In conclusion, we have identified overexpression of Evi‐1 oncoprotein as a novel mechanism by which a subset of human CRCs may escape TGF‐β regulation. We have also identified a novel Evi‐1 transcript, Evi‐1e, as the major Evi‐1 transcript expressed in human CRCs. © 2011 Wiley Periodicals, Inc.